Peranan Sistem Informasi Padi Better Rice Initiative Asia (BRIA) Dalam Mendukung Ketersediaan Pangan Daerah - Isnaini Isnaini; Sirojuzilam Sirojuzilam; Agus Purwoko (Fakultas Teknik, 2018)
This study is aimed at studying the projection of harvested area and production for 10 years, the influence of rice cultivation technology on increasing rice production and the role of BRIA Rice Information System to food availability system in Serdang Bedagai District. The data collected were primary and secondary data that analyzed by linier regression to figure out the projection of harvested area and production, logistic regression to recognize the influence of rice cultivation technology on increasing rice production and FGD to figure out the role of BRIA Rice Information System in favorregional food availability. The result of this study showed that there was an upward trend in harvested area and production in Serdang Bedagai District of 2012-2022. Rice cultivation technologies have given significant influence to increase rice production. BRIA Rice Information System has played a part of supporting real-time data and information to support the regional food availability.